Compensating affection deprivation through K-drama - Muqaromah, Susiana Febriyanti; Syahrivar, Jhanghiz (Expose: Jurnal Ilmu Komunikasi, 2024)
K-drama is arguably one of the most popular media businesses of the century. Previous studies suggest that affection deprivation signifies an absence of meaningful communication and affectionate relationships with significant others, leading to various negative affective states such as anxiety, stress, and depression. A less explored compensatory strategy for affection deprivation in the Asian context is K-drama addiction, as in binge-watching and parasocial relationships with Korean celebrities and fictional characters. This phenomenological study investigates how affection deprivation influenced K-drama addiction during the COVID-19 pandemic. This study used a purposive sampling involving female K-drama fans who engaged in binge-watching and reported addiction symptoms. Several themes emerged during the in-depth interviews and focus group discussions: affection deprivation, negative affect, compensatory strategy, perceived benefits, enabling factors, and the cycle of addiction. This paper is the first study that attempts to link K-drama addiction with compensatory consumption.